2023
DOI: 10.3390/foods12071371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Frying Process on the Flavor Variations of Allium Plants

Abstract: The Allium plant is widely used in cuisines around the world for its characteristic flavor. The general profile of the plant changes a lot and presents quite different smells after the frying process. In this work, five Allium plants and their fried oils were compared to find out how the frying process impacts the general flavor profile. The results of sensory analysis indicated that the frying process could substantially increase the flavor acceptability of fresh Allium plants. Meanwhile, according to gas chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…2-vinyl-4H-1,3-dithiin increased in fried garlic (Table 1). Other studies have also shown an increase in 2-vinyl-4H-1,3dithiin [19][20][21]. Allicin transforms into vinyl dithiins in non-polar solvent so 2-vinyl-4H-1,3dithiin was expected to increase when the garlic was fried in oil [22].…”
Section: Effect Of Frying On Raw Garlic Volatilesmentioning
confidence: 92%
See 1 more Smart Citation
“…2-vinyl-4H-1,3-dithiin increased in fried garlic (Table 1). Other studies have also shown an increase in 2-vinyl-4H-1,3dithiin [19][20][21]. Allicin transforms into vinyl dithiins in non-polar solvent so 2-vinyl-4H-1,3dithiin was expected to increase when the garlic was fried in oil [22].…”
Section: Effect Of Frying On Raw Garlic Volatilesmentioning
confidence: 92%
“…The levels of allyl methyl disulfide, diallyl disulfide, allyl mercaptan and allyl methyl sulfide were decreased by 75 to 99% by frying (Table 1). Other studies have also shown that frying garlic causes a significant loss of sulfur volatile compounds including diallyl disulfide, allyl methyl sulfide and allyl mercaptan [19][20][21]. Frying breaks down the sulfur-containing compounds in garlic, leading to a decrease in its characteristic malodorous odor-producing volatiles.…”
Section: Effect Of Frying On Raw Garlic Volatilesmentioning
confidence: 99%
“…Taxonomically, green onion belongs to the division angiosperms, class Liliopsida, order Asparagale, family Amaryllidaceae, genus Allium and species fistulosum. The crop has unique botanical features that make it distinct from its close relatives, the common onions (Allium cepa), leeks (Allium ampeloprasum), chives (Allium schoenoprasum) and garlic (A. sativum) [24]. For instance, though they have a mild onion-like flavor, unlike the bulb-forming Allium species (such as common onions and garlic), green onions are generally non-bulb-producing and notable for their slender green stalks [25] used in traditional medicine and mild onion flavor [26].…”
Section: Characteristics Of Allium Fistulosummentioning
confidence: 99%
“…Green onions have been cultivated and consumed for centuries across various cultures [33]. At present, the cultivation and consumption of the crop have transcended geographical boundaries, becoming an integral part of many culinary traditions [24]. Different cultivars of green onions exhibit variations in appearance and pungent flavor and aroma, influenced mainly by their organosulfur compounds [34].…”
Section: Cultural and Culinary Applicationsmentioning
confidence: 99%
See 1 more Smart Citation